College students’ educational experiences amid COVID-19 pandemic (Journal of Applied Learning and Teaching, 2021)
Introduction: While lockdown and shelter-at-home strategies enforced by governments were critically needed to contain the rapid progression of the COVID-19 virus, in the U.S., hundreds of millions of learners and higher education institutions were significantly impacted with their daily operations. This study looks at the COVID-19 impact on higher education, with an emphasis on technology, mental health, and resources provided by the university. Methods: We utilized primarily qualitative research methods to assess students’ responses of our survey and examined emerging themes. We analyzed each question for word order and identified phrases and keywords students provided. Results: Our findings show that 42% of the participants did not find online education to be difficult nor did they have any technical difficulties, and this is promising for the future of virtual education. On the other hand, 58% of the students found the whole experience to be challenging, owing to a number of reasons (internet access, Blackboard knowledge, lacking motivation, and instruction related challenges). In terms of stress/anxiety levels, at least 88% of the students were stressed due to multiple factors (i.e., catching COVID-19, financial difficulties, staying engaged, finding childcare, maintaining relationships, losing family members). Interestingly, 82% of the students reported not using campus-provided virtual workshops. Conclusion: Recommendations for improvement are provided.